Taxonomic and molecular assessment of the apparently alien and cosmopolitan Nereididae Blainville, 1818 polychaetes from South Africa - Kara, Jyothi (Stellenbosch : Stellenbosch University, 2019)
Thesis (PhD)--Stellenbosch University, 2019.